Knowing and the truth: Three histories of Daugo Island, Papua New Guinea. (9th June 2013) - Goddard, Michael
Abstract : Courts of law in Melanesian countries, particularly in the aftermath of the colonial period, have attempted to accommodate 'custom'. In Papua New Guinea they commonly hear land claims under terms of reference that acknowledge the wide variety of customs among the many ethno‐linguistic groups comprising the nation. A corollary of this liberalism is that, in theory, they admit 'traditional evidence' including legends and myths. Yet as courts of law they are required to apply some criteria of proof and to search for the 'truth' by examining the 'facts'. A long‐running land case from Papua New Guinea and its aftermath raises interesting questions about what happens when oral history encounters these legal imperatives, and may help us appreciate why Melanesians often do not regard a court's decision as final.